2001
DOI: 10.1002/jsfa.923
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of the efficiency of transfer of L‐histidine from blood to milk when it is the first‐limiting amino acid for secretion of milk protein in the dairy cow

Abstract: The ef®ciency of transfer of L-histidine into milk protein was measured in two experiments in which L-histidine was infused intravenously into dairy cows eating a basal diet of grass silage and a cereal-based supplement containing feather meal. Both experiments used Latin square designs, and infusion periods lasted 10 days. In Experiment 1, histidine was infused alone at doses of 3, 6 and 9 gday À1. The output of milk protein increased up to the 6 g day À1 dose but fell back to the basal level when 9 g day À1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
33
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 13 publications
7
33
1
Order By: Relevance
“…However, the same cannot be said for calculated AA "imbalances" at the intestinal absorptive site. In most cases an estimated imbalance of AA manifests as increased milk fat content, or a low ratio of protein:fat in milk (Chamberlain et al, 1992;Varvikko et al, 1999;Robinson et al, 2000;Cant et al, 2001;Kim et al, 2001;Weekes et al, 2006) possibly through mechanisms in the mammary gland, such as increased blood flow to maintain milk protein yield, thereby supplying more milk fat precursors to stimulate milk fat yield (Cant et al, 2001;Weekes et al, 2006). It has been suggested that endocrine responses to total AA imbalances can override imperfections in AA profiles in order to maintain milk protein yields (Weekes et al, 2006), although not all of the resulting changes may be deemed positive by dairy farmers.…”
Section: Discussionmentioning
confidence: 99%
“…However, the same cannot be said for calculated AA "imbalances" at the intestinal absorptive site. In most cases an estimated imbalance of AA manifests as increased milk fat content, or a low ratio of protein:fat in milk (Chamberlain et al, 1992;Varvikko et al, 1999;Robinson et al, 2000;Cant et al, 2001;Kim et al, 2001;Weekes et al, 2006) possibly through mechanisms in the mammary gland, such as increased blood flow to maintain milk protein yield, thereby supplying more milk fat precursors to stimulate milk fat yield (Cant et al, 2001;Weekes et al, 2006). It has been suggested that endocrine responses to total AA imbalances can override imperfections in AA profiles in order to maintain milk protein yields (Weekes et al, 2006), although not all of the resulting changes may be deemed positive by dairy farmers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Leu produced a dosedependent regulation of mTOR and served as a key intracellular regulatory factor of the mTORC1 pathway in CMECs (Moshel et al, 2006;Prizant and Barash, 2008;Appuhamy et al, 2012;Durán and Hall, 2012). Kim et al (2001) found that His was the first limiting factor for milk protein secretion. Some traditional experiments indicated that the perfusion of His promoted milk protein synthesis (Bequette et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In current dairy production systems, an average of 25% of dietary N is captured in milk, which results in approximately 75% of the dietary N being excreted in urine and feces (Hristov et al, 2004;Arriola Apelo et al, 2014b). Feeding animals with low-protein diets (Kalscheur et al, 2006) and supplementation of those deficient EAAs (lysine (Lys), methionine, leucine (Leu), isoleucine, valine, and histidine (His)) may maintain production, which can improve the total N efficiency (Kim et al, 2001;Wang et al, 2010;Appuhamy et al, 2011a;, which is in accordance with Liebig's hypothesis on developing the concept of the order of LAAs. This concept is commonly described by using the analogy of a water barrel with broken staves (Appuhamy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, intravenous infusion of 9 g . d -1 of histidine reduced the yield of milk protein compared with a lower dose, which implies that histidine given in higher doses was beyond the level that is limiting for milk production and milk protein synthesis in dairy cows (Kim et al, 2001b).…”
Section: Discussionmentioning
confidence: 99%